Seroprevalence of Hepatitis B and Hepatitis C among Blood Donors at Dharan, Sunsari, Nepal - Rai, Sabina; Dongol, Pranita; Khanal, Hemanta (Sunsari Technical College Journal, 2016)
Hepatitis B and Hepatitis C are the chronic viral infection that might be transmitted by blood transfusion. Nepal is known to have lowest seroprevalence in Asia. The main objective of the present study is to find out the prevalence of hepatitis B and Hepatitis C and their co-infection among blood donors during study period from March to August 2014. This was a cross sectional study among volunteer blood donors in Dharan who had donated the Blood. A total of 4930 donated blood samples were collected and screened for hepatitis B and hepatitis C by using a rapid enzyme immunoassay (EIA) technique. Among 4930 blood samples under study, the overall seroprevalence of hepatitis B were 0.22% (11 out of 4930) and hepatitis C were 0.39% (19 out of 4930) (P value = 0.01) and the prevalence being lower in females than males for both cases. Hepatitis B were more in age group of 21 -30 (0.4%) but hepatitis C in age group of 31-40 (0.5%). Hepatitis B and C are potential threats to be transmitted from unscreened blood. Sunsari Technical College Journal 2015, 2(1):13-16